Analisis Kinerja Pegawai Fraksi Gerindra di Kantor DPRD Sumatera Utara - Kevin Orama Singarimbun; Abu Syahrin; Novi Kartika; Rohinur Annasari Harahap (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
Article 14 of the DPRD Rules of Procedure explains that a fraction is a grouping of DPRD members according to the configuration of political parties produced by general elections (elections). Meanwhile, the requirements for political parties have been regulated in the Political Party Law, as in Article 2, Paragraph 1 of 2008, the Political Party Law explains that, “a Political Party is established and formed by at least 50 Indonesian citizens aged 21 years with a notary deed”. So that each group people cannot arbitrarily form Political Parties. Keyword: Analisis, Performance,DPRD,Gerindra